The effects of conjugated linoleic acid on growth and lipid profiles in serum and liver tissue of type-2 diabetes mellitus model rat - Yohanes Buang; Yu-Ming Wang; Teruyoshi Yanagita (Journal of Applied Chemical Science, 2012)
Conjugated linoleic acid (CLA) refers to a group of positional and geometric conjugated-dienoic isomers of linoleic acid. This chemical has been suggested to have antidiabetic activity. However, the effects of CLA on growth parameters and lipid profiles in serum and liver tissue of type-2 diabetic subjects have no data reported. The present study was conducted to elucidate the effects of CLA on growth parameters and the lipid profiles in serum and liver tissue of male Otsuka Long-Evans Tokushima Fatty rat, as a model of type-2 diabetes. The final body weight and the liver weight were nearly similar between the groups but the white adipose tissue (WAT) weight decreased, although it failed to reach significant level (P<0.05). Serum high density lipoprotein levels moderately increased, it was approximately by 6%, in which the increase was accompanied with a reduction of atherogenic index slightly (Control = 1.00±0.02, while the treatment group = 0.95±0.03). Furthermore, the liver triglycerides (TG) content decreased by 13%. The similar final body weight accompanied with reductions of WAT level and liver TG content might indicate that CLAs diets have management properties on body fat and liver TG metabolism in patients with type-2 diabetes mellitus.